Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $p(t)=P(e^{it})=r(t)e^{it}$, where $r(t)>0$ is a mapping between $[0,2π]$ i.e. between the unit circle $T$ and a curve, then it seems that $\mathrm{Lip}(p)=\mathrm{Lip}(P)$ but I have't the proof.

share|cite|improve this question
I doubt it. Try this example: $r(t)=1+\epsilon \cos 2t$.. it may or may not work. – user31373 Jul 12 '12 at 19:40
@LeonidKovalev It is not a good example. Maybe some complicated example should be given. – Marijan Jul 12 '12 at 20:06
It is possible to prove that $\text{Lip}(p)\le \text{Lip}(P)$. Let $f:[0,2\pi) \to S^1, f(t)=e^{it}$ (which is clearly invertible, with inverse $g:S^1\to [0,2\pi), g(z)=\arg z\mod 2\pi$.) For every $t,s \in [0,2\pi)$ with $t\ne s$ we have $$ \frac{|p(t)-p(s)|}{|t-s|}=\frac{|P(f(t))-P(f(s))|}{|f(t)-f(s)|}\cdot\frac{|f(t)-‌​f(s)|}{|t-s|}\le \text{Lip}(P)\text{Lip}(f). $$ Since $\text{Lip}(f)=1$, it follows that $\text{Lip}(p) \le \text{Lip}(P)$. As for the other inequality I can't tell whether it's true! – Mercy King Jul 12 '12 at 23:52
@Mercy Of course this direction is trivial, because $|e^{it}-e^{is}|\le |t-s|$. – Marijan Jul 13 '12 at 6:15
up vote 0 down vote accepted

Turns out this is true. We may assume that $\mathrm{Lip}(p)=1$, that is, $\dot r^2+r^2\le 1$ where the dot indicates derivative with respect to $t$. Note that $r\le 1$. Our goal is to show that $|r(t)e^{it}-r(0)|\le |e^{it}-1|$ for all $t$. After squaring this simplifies to $$(1)\qquad \qquad 2\cos t\,(1-r(0)r(t))\le 2-r(0)^2-r(t)^2$$ which is trivially true when $\cos t\le 0$. So we only have to deal with $0<t<\pi/2$.

We lose no generality in assuming that $r(t)\le r(0)$. It is convenient to write $r(0)=\cos \alpha$ where $0\le \alpha\le \pi/2$. Integrating differential inequality $\dot r\ge -\sqrt{1-r^2}$, we find that $r(t)\ge \cos(\alpha+t)$. The inequality (1) can be written as $$(2)\qquad\qquad r(t)^2-2r(t)\cos\alpha\cos t+\cos^2\alpha-2(1-\cos t)\le 0$$ Since the left hand side is a convex function of $r(t)$, it suffices to verify (2) at the endpoints $r(t)=\cos(\alpha+t)$ and $r(t)=\cos\alpha$.

Plugging $r(t)=\cos(\alpha+t)$ into (2) we get $-(1-\cos t)^2\le 0$. Plugging $r(t)=\cos \alpha$ into (2) we get $-2\sin^2 \alpha \, (1-\cos t)\le 0$. QED

There are somewhat similar lemmas in Radial extension of a bi-Lipschitz parametrization of a starlike Jordan curve by Kalaj and in On quasiconformal self-mappings of the unit disk satisfying Poisson's equation by Kalaj and Pavlović, although in both cases they are about modulus-preserving maps rather than argument-preserving.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.